2009
DOI: 10.1021/jm900615h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antimicrobial Evaluation of Amphiphilic Neamine Derivatives

Abstract: The aminoglycoside antibiotics bind to the 16S bacterial rRNA and disturb the protein synthesis. One to four hydroxyl functions of the small aminoglycoside neamine were capped with phenyl, naphthyl, pyridyl, or quinolyl rings. The 3',4'- (6), 3',6- (7a), and the 3',4',6- (10a) 2-naphthylmethylene derivatives appeared to be active against sensitive and resistant Staphylococcus aureus strains. 10a also showed marked antibacterial activities against Gram (-) bacteria, including strains expressing enzymes modifyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(87 citation statements)
references
References 31 publications
3
83
0
1
Order By: Relevance
“…Antibacterial activity of amphiphilic tobramycin R Dhondikubeer et al and others, 7,8 which have shown that conversion of the nonamphiphilic aminoglycosides neomycin-B and kanamycin-A into amphiphilic aminoglycosides enhances antibacterial activity against aminoglycoside-resistant and multidrug-resistant Gram-positive bacteria. [3][4][5] The compounds were selected to explore how the nature of the cationic aminoglycoside-based headgroup, the number of cationic charges and the nature of the hydrophobic lipid tail affects antibacterial activity in this class of compounds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibacterial activity of amphiphilic tobramycin R Dhondikubeer et al and others, 7,8 which have shown that conversion of the nonamphiphilic aminoglycosides neomycin-B and kanamycin-A into amphiphilic aminoglycosides enhances antibacterial activity against aminoglycoside-resistant and multidrug-resistant Gram-positive bacteria. [3][4][5] The compounds were selected to explore how the nature of the cationic aminoglycoside-based headgroup, the number of cationic charges and the nature of the hydrophobic lipid tail affects antibacterial activity in this class of compounds.…”
Section: Resultsmentioning
confidence: 99%
“…[3][4][5][6][7] For instance, when compared with their parent aminoglycosides, both neomycin-B-based hexacationic C 16 -lipid 7 or kanamycin-A-based tetracationic lipid C 16 -lipid 6 ( Figure 1) displayed 64-to 32-fold enhanced antibacterial activity against methicillin-resistant Staphylococcus aureus, whereas a 4-to 8-fold decrease in MIC was observed against two Pseudomonas aeruginosa strains. 4 Similarly, conjugation of neomycin-B and kanamycin-A to an ultrashort hydrophobic dipeptide led to a 16-fold lower MIC against methicillin-resistant Staphylococcus aureus and a 4-to 32-fold lower MIC against Pseudomonas aeruginosa strains.…”
Section: Introductionmentioning
confidence: 99%
“…The outer membrane of Pseudomonas is considered particularly impermeable due to the unusual tight packing of acyl chains. In the search for new antibiotics active on bacterial membranes, we synthesized a library of more than 60 amphiphilic neamine derivatives (27,29,30). Three 3=,6-dialkyl neamine derivatives (3=,6-diNn, 3=,6-di2NP, and 3=,6-di2NB) were shown to be active against Gram-positive and Gram-negative strains and to have low cytotoxicity (29).…”
Section: Discussionmentioning
confidence: 99%
“…The 3=, 6- [(2Љ-naphthyl)methyl]neamine (3=,4=,6-tri2NM) derivatives (Fig. 1) were synthesized in three steps from neamine according to our previous reports (27,29,30) by (i) tritylation of the four amine functions, (ii) alkylation with 1-bromononane or the corresponding bromonaphthylalkane in dimethyl formamide (DMF) in the presence of NaH or under phase transfer conditions with toluene and a concentrated aqueous solution of sodium hydroxide using tetrabutylammonium iodide or fluoride as the phase transfer agent, and (iii) removal of the trityl protective groups in the presence of trifluoroacetic acid-anisole. All compounds were isolated as tetratrifluoroacetates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation